2014
DOI: 10.1002/stem.1639
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Wnt/β‐Catenin Signaling Determines Dorsalization of the Postnatal Subventricular Zone and Neural Stem Cell Specification into Oligodendrocytes and Glutamatergic Neurons

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
110
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 79 publications
(124 citation statements)
references
References 34 publications
(86 reference statements)
13
110
1
Order By: Relevance
“…6A-C). Similarly, canonical Wnt signaling is active exclusively in the dorsal V-SVZ and within dorsally derived lineages (Ortega et al, 2013;Azim et al, 2014b), in agreement with its described role in dorsalization and caudalization of the developing telencephalon (Lee et al, 2000;Muzio et al, 2005;Hoch et al, 2009) (Fig. 6A-C).…”
Section: Spatial Patterns In the V-svz Provide Insights Into The Mechsupporting
confidence: 85%
See 1 more Smart Citation
“…6A-C). Similarly, canonical Wnt signaling is active exclusively in the dorsal V-SVZ and within dorsally derived lineages (Ortega et al, 2013;Azim et al, 2014b), in agreement with its described role in dorsalization and caudalization of the developing telencephalon (Lee et al, 2000;Muzio et al, 2005;Hoch et al, 2009) (Fig. 6A-C).…”
Section: Spatial Patterns In the V-svz Provide Insights Into The Mechsupporting
confidence: 85%
“…For example, antagonists of the Wnt signaling pathway are highly upregulated with aging and their ablation reverses the agerelated decline in neurogenesis (Seib et al, 2013). In the case of the V-SVZ, microdissection of defined microdomains followed by RNA or protein extraction can be performed to study the differential expression of TFs and/or the activity of signaling pathways (Azim et al, 2014b(Azim et al, , 2015 (Fig. 6D).…”
Section: Beyond Space: Adding the Temporal Dimensionmentioning
confidence: 99%
“…Activation of -catenin signaling increases the numbers of oligodendrocytes derived from this neurogenic site, while inhibition seems to reduce the glial cell number [142]. In another study, -catenin activation via GSK-3 inhibition increased cell proliferation in the SVZ, and this was accompanied by increased numbers of oligodendrocytes [143], confirming an earlier study that highlighted oligodendrocytic genes as targets of -catenin [144]. Thus, Wnt/ -catenin signaling may also play important roles in the proliferation of progenitors and in oligodendrocytic development in the SVZ.…”
Section: Wnt Signaling and Adult Neurogenesis: Intracellular Componentsmentioning
confidence: 94%
“…Nevertheless, it has been shown that several specific signaling are different between compartments. For example, the Wnt family of soluble ligands regulates the self-renewal of a small population of V-SVZ astrocytes, which are located in the dorsal compartment and generate glutamatergic olfactory bulb neurons (Azim et al 2014). Another example is the sonic hedgehog (Shh) signaling.…”
Section: Introductionmentioning
confidence: 99%